Penegakan Hukum Bagi Muncikari Penyedia Fasilitas Jarīmah Ikhtilāṭ di Kota Banda Aceh: (Studi Kasus Polresta Banda Aceh) - Ari Wilanda; Irwansyah (Jarima: Jurnal Ilmiah Mahasiswa Hukum Pidana Islam, 2025)
The practice of pimping in the country of Sharia Aceh, especially in Banda Aceh City, has become a social, moral and legal polemic that still needs serious attention from many parties. In fact, there are cases of pimps providing jarimah ikhtilāṭ facilities. For this reason, the legal aspects to be studied are the law enforcement carried out by Banda Aceh Police for pimps providing jarīmah ikhtilāṭ facilities from the perspective of Qanun Number 6 of 2014 concerning Jinayat Law. This research study uses a statutory approach and conceptual approach, with the nature of the analysis is descriptive-analysis. The types of criminal acts of pimps in jarīmah ikhtilāṭ that occur in Banda Aceh City are in the form of providing facilities or places to commit jarīmah ikhtilāṭ, then in the form of intermediaries between customers and prostitutes. Pimps find prostitutes or prostitutes themselves who ask to find customers. Law enforcement carried out by Banda Aceh Police for pimps is in accordance with the provisions of Qanun Number 6 of 2014 concerning Jinayat Law.